Localized Surface Plasmon Resonances with Spherical Metallic Nanoparticles - Ngo, Minh Quang (Communications in Physics, 2018)
In this work we review in part of our recent theoretical study on the electrical intensity enhancement in the dielectric medium surrounding metallic nanoparticles due to the effect of their localized surface plasmon resonance (LSPR). The known results in the case of a simple metallic spherical nanoparticle are presented and then extend them to the general case of complex network of the identical spherical metallic nanoparticles. For illustration, several typical lattices of identical spherical metallic nanoparticles will be treated. The findings of electrical intensity enhancements and plasmonic resonance wavelengths of the single and the network of the metallic nanoparticles are obtained based on the analytical expressions. The theoretical results were compared and shown the good agreement with simulation results. The simulation of the LSPRs and the electrical intensity enhancements was performed using the boundary element method.